Sediment flux‐driven channel geometry adjustment of bedrock and mixed gravel–bedrock rivers. Issue 14 (18th September 2020) - Baynes, Edwin R.C.; Lague, Dimitri; Steer, Philippe; Bonnet, Stéphane; Illien, Luc
Abstract: Sediment supply ( Q s ) is often overlooked in modelling studies of landscape evolution, despite sediment playing a key role in the physical processes that drive erosion and sedimentation in river channels. Here, we show the direct impact of the supply of coarse‐grained, hard sediment on the geometry of bedrock channels from the Rangitikei River, New Zealand. Channels receiving a coarse bedload sediment supply are systematically (up to an order of magnitude) wider than channels with no bedload sediment input for a given discharge. We also present physical model experiments of a bedrock river channel with a fixed water discharge (1.5 l min −1 ) under different Q s (between 0 and 20 g l −1 ) that allow the quantification of the role of sediment in setting the width and slope of channels and the distribution of shear stress within channels. The addition of bedload sediment increases the width, slope and width‐to‐depth ratio of the channels, and increasing sediment loads promote emerging complexity in channel morphology and shear stress distributions. Channels with low Q s are characterized by simple in‐channel morphologies with a uniform distribution of shear stress within the channel while channels with high Q s are characterized by dynamic channels with multiple active threads and a non‐uniform distribution of shear stress. We compare bedrock channel geometries from the Rangitikei and the experiments to alluvial channels and demonstrate that the behaviour is similar, with a transition from single‐thread and uniform channels to multiple threads occurring when bedload sediment is present. In the experimental bedrock channels, this threshold Q s is when the input sediment supply exceeds the transport capacity of the channel. Caution is required when using the channel geometry to reconstruct past environmental conditions or to invert for tectonic uplift rates, because multiple configurations of channel geometry can exist for a given discharge, solely due to input Q s . © 2020 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd Abstract : The graphical abstract shows the main findings from both the field case study, the Rangitikei River, New Zealand, and the experimental modelling. There is a clear impact of coarse bedload sediment on the channel geometry.